Intended vs. unintended consequences of migration restriction policies: Evidence from a natural experiment in Indonesia - Mattia Makovec; Ririn Purnamasari; Matteo Sandi; Astrid Savitri (University of Essex, Institute for Social and Economic Research (ISER), 2016)
We study the consequences of a series of migration policies that restricted the migration of Indonesian female domestic workers towards traditional destinations, namely Malaysia and Saudi Arabia. Our difference-in-differences specification exploits the differential impact across Indonesian villages of this unique natural experiment, intended to stop repeated cases of mistreatment of Indonesians working overseas. Our results suggest that the moratoria had negative effects on economic activity and households' welfare, and worsened labor market conditions, especially for women, in the origin communities. Our results highlight the unintended effects that migration restrictions may have precisely on those they were intended to benefit.
Keywords: O15; J61; O53; 330; labor migration; migration policy; female migrants; migration restrictions; local labor markets; Indonesia